Successful management of refractory epilepsy in creatine transporter deficiency with cannabidiol and clobazam: A case report - Maria Borrell‐Pichot; Carmen Fons; Susana Boronat; Alba Sierra‐Marcos (Epilepsia Open)
Abstract Creatine transporter deficiency (CRTR‐D) is a rare X‐linked inherited disease belonging to the group of cerebral creatine deficiency disorders. Major clinical features include developmental delay and epilepsy. To date, fewer than 200 individuals with CRTR‐D have been reported. As a result, there is little evidence for effective treatment. Available therapies are creatine precursors, with a mild effect on disease progression. Concerning epilepsy, standard management is recommended and no specific anti‐seizure medication (ASM) has been shown to be effective in refractory cases. We report the case of a 28‐year‐old male patient with CRTR‐D and childhood‐onset refractory epilepsy. He had an average of 10–20 focal motor seizures with impaired consciousness per month. He had tried several ASMs without significant improvement. Treatment with cannabidiol (CBD) and clobazam (CLB) in combination was added. The patient became seizure‐free from the first week, and up to 1 year of follow‐up. Behavioral improvement was also noted by his caregivers. No adverse effects were reported. Very few cases of CRTR‐D with refractory epilepsy have been reported. This calls for more extensive research and suggests a possible role for CBD in cerebral creatine metabolism and transport and valuable option for future studies. Plain Language Summary Creatine transporter deficiency (CRTR‐D) is a rare genetic disorder causing mental, behavioral, and movement problems. More than half of patients also have seizures, but because there are fewer than 200 known cases, it is difficult to know the best treatment options. We present a 28‐year‐old man with CRTR‐D who had severe developmental delays and frequent seizures since childhood, despite trying many medications. After starting cannabidiol and clobazam, he has been seizure‐free for a year. Sharing this success might help other people with CRTR‐D benefit from similar treatments.